Raising the bar (17). Issue 3 (3rd July 2021) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Chasco, Coro; Corrado, Luisa; Ditzen, Jan; Doran, Justin; Felsenstein, Daniel; Fuerst, Franz; Le Gallo, Julie; McCann, Philip; et al.
ABSTRACT: This editorial summarizes the papers published in issue 16(3) (2021) in order to raise the bar in applied spatial economic research and highlight new trends and knowledge. The first paper analyses the economic consequences of the rise and spread of the Covid-19 virus in the Brazilian state of São Paulo. The second paper presents a multi-regional generalized RAS technique to update input–output tables. The third paper investigates which European Union regions are most likely to be exposed to external shocks and which are more resilient. The fourth paper proposes a new neighbourhood inequality index for cities. The fifth paper analyses productivity and profitability using a sophisticated hierarchical model applied to a huge data set of individual firms. The sixth paper contains an empirical analysis on the choice of the national capital city location among 80 potential candidates in China over a period of 2240 years. The seventh paper explains political ideology at the municipality level in Switzerland based on 312 federal referendums between 1981 and 2017. The eighth paper examines the driving forces of business cycle synchronization among the 49 US states.